Flexible and excellent electromagnetic interference shielding film with porous alternating PVA-derived carbon and graphene layers - Jiatong Li; Jinzhe Li; Tian Li; Zhengkang Xu; Yao Chen; Likui Zhang; Qing Qi; Benliang Liang; Fanbin Meng (iScience, 2023)
Summary: Recently, the design of graphene-based films with elaborately controlled microstructures and optimized electromagnetic interference shielding (EMI) properties can effectively improve EM energy attenuation and conversion. Herein, inspired by the structure of multi-layer steamed bread, an alternating multilayered structure with polyvinyl alcohol (PVA)-derived carbon layers and graphene/electrospun carbon nanofibers layers was designed through alternating vacuum-assisted filtration method. The composite film exhibited favorable impedance matching, abundant loss mechanism, and excellent EMI shielding ability, resulting in absorption dominated shielding characteristic. Thus, the resultant 7-layer alternating composite films with a thickness of 160 μm achieved an EMI shielding effectiveness (EMI SE) of up to 80 dB in the X-band. Specially, finite element analysis was applied to demonstrate the importance of seven-layer film alternations and detailed analysis of electromagnetic shielding mechanisms. Taken together, this effort opens a creative avenue for designing and constructing flexible composite films with excellent EMI shielding performance.